2019
DOI: 10.1186/s40780-019-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug use positively correlates with high-risk prescriptions in the Japanese elderly: a longitudinal study

Abstract: Background There is a lack of evidence that multidrug use triggers adverse events. Therefore, the main purpose of this study was to clarify the relationship between the total number of drugs and number of high-risk prescriptions administered to Japanese elderly patients. Methods Using hospital electronic medical records (EMR), we evaluated the prescriptions of outpatients aged 65 years or older. We defined prescriptions of potentially inappropriate medications (PIMs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…Cross-sectional studies in Japan have reported that patients who were prescribed by two or more physicians or who consulted more medical institutions are more likely to have PP and PIM use [8,70], as shown in our study. Furthermore, our study demonstrated that there is also a significant association between PP and PIM use, which is supported by previous reports [8,[20][21][22][23][24][25][26][27]. The frequency of elderly PIM(+) patients in Japan varies from 22.9% to 67.3% [8,22,23,27,31,35,68,71,72] because of different study populations and settings, different definitions of PIMs, or different timings of the investigation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Cross-sectional studies in Japan have reported that patients who were prescribed by two or more physicians or who consulted more medical institutions are more likely to have PP and PIM use [8,70], as shown in our study. Furthermore, our study demonstrated that there is also a significant association between PP and PIM use, which is supported by previous reports [8,[20][21][22][23][24][25][26][27]. The frequency of elderly PIM(+) patients in Japan varies from 22.9% to 67.3% [8,22,23,27,31,35,68,71,72] because of different study populations and settings, different definitions of PIMs, or different timings of the investigation.…”
Section: Discussionsupporting
confidence: 88%
“…Potentially inappropriate medications (PIMs), defined as medications with more harmful than beneficial effects on elderly patients [19], are closely related to PP [8,[20][21][22][23][24][25][26][27] and are a relevant public health concern for elderly patients [28,29]. In 2015, the Japan Geriatric Society (JGS) updated the "Guidelines for Medical Treatment and its Safety in the Elderly" and proposed medication lists regarding PIMs, "Screening Tool for Older Persons' Appropriate Prescriptions for Japanese" (STOPP-J), to contribute to improving prescription quality [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have shown, in a population of elderly subjects living in nursing homes, that an increase in the anticholinergic burden of prescriptions is associated, on the one hand, with polypharmacy and, on the other hand, with prescription of PIMs. Other studies have suggested an association between polypharmacy and prescription of PIMs [17], but as far as we are aware, there are no studies analysing simultaneously the association between polypharmacy, anticholinergic burden and number of PIMs. Polypharmacy and prescription of PIMs are known risk factors for drug‐induced iatrogenic disorders [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, little is known about the utility of such approaches in the outpatient setting/ambulatory care. The negative impact of potentially inappropriate medications has been robustly demonstrated in older outpatients as well [ 11 ]. The main challenge, however, remains how to address this problem.…”
Section: Discussionmentioning
confidence: 99%